Electrical conductivity and dielectric studies of MnO2 doped V2O5 - Tan, Foo Khoon; Hassan, Jumiah; Abd. Wahab, Zaidan; Azis, Raba'ah Syahidah (Elsevier, 2016)
The investigation on electrical conductivity and dielectric properties of mixed oxide of manganese (Mn) and vanadium (V) was carried out to study the mixed oxides response to different frequencies and different measuring temperatures. The frequency and temperature dependence of AC conductivity, dielectric constant and dielectric loss factor of mixed oxides were studied in the frequency range of 40 Hz–1 MHz and a temperature range of 30–250 °C. Since the mixed oxides are multi phase materials, hence the properties of the pure oxides are also presented in this study to discuss the multi phase behaviour of the mixed oxides. The XRD pattern shows the Mn–V oxide is multiphase and quantitative phase analysis was performed to determine the relative phases. The overall results indicate that with increasing temperature, the AC conductivity, dielectric constant, dielectric loss factor and loss tangent of the Mn–V mixed oxide increases. However, it shows an overlap in the dielectric constant at 225 °C and 250 °C due to the V2O5 phase in the mixed oxide. From the AC activation energy, the mixed oxides underwent conduction mechanism transition from band to hopping in the investigated frequency range. The MnV2O6 has relatively good resistivity, therefore the mixed oxide sintered at 550 °C with the highest composition of MnV2O6 gives the highest dielectric constant of 9845 at 1 kHz, and at 250 °C.